An analytical cross sectional study on psychosocial stressors and psychiatric morbidity in acute myocardial infarction in a tertiary care teaching hospital - Suresh K Kumar; Bhataraju Prabhuram; Pavan V T Kumar; Phani D Bhushan (Archives of Mental Health, 2016)
Background: Psychiatric stressors and morbidity can be both cause and effect of myocardial infarction. Various life events acting as psychological stressors can precipitate acute myocardial infarction. Acute MI can lead to plethora of psychiatric morbidities, including various degrees of depression and anxiety. Studies from India are scarce on the subject. Aims and objectives: To assess the occurrence of stressful life events and level of psychiatric morbidity (anxiety and depression) in the post myocardial infarction period among myocardial infarction patients and to compare them with a randomly selected non-myocardial infarction control group. Methods: The study was an analytical cross sectional study, conducted in a tertiary care teaching hospital. The study subjects consisted of 50 patients with present acute MI episode, 50 post MI subjects after 6 months of MI episode and 50 healthy controls. Presumptive Stressful Life Event Scale (PSLES) was used to assess stressful life events, DSM-IV TR Diagnostic criteria and Hamilton Depression Rating Scale (HAM-D) and Hamilton Anxiety Rating Scale (HAM-A) were used to assess the severity of depression/anxiety. Results: The proportion of people with 2 or more stressors was higher in MI group, compared to non MI group (82% Vs 60%). The proportion of moderate and severe depression was 34% and 10% in post MI group, where as it was 2% and 0% in control group. The proportion of subjects with anxiety was higher among post MI group, compared to controls. The proportion of moderate and severe anxiety was 12% and 24% in post MI group, where as none of the subjects in control group had anxiety. Conclusions: There is a strong association between stressful life events, depression, anxiety and Myocardial infarction.